2016
DOI: 10.1007/s00059-016-4492-7
|View full text |Cite
|
Sign up to set email alerts
|

New implantable cardiac monitor with three-lead ECG and active noise detection

Abstract: BioMonitor effectively detects patients with bradycardia, tachycardia, AF, or asystole. Active noise detection seems to reduce the transmission of meaningless data without diminishing the positive predictive value of the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…As in this study, most of the studies were conducted using external Holter monitoring as a criterion standard for the presence or absence of AF. Biotronik ILRs have evaluated the performance of AF algorithms through two separate studies [22,23]. As most of the AF episodes confirmed on the Holter were detected on the ILR, they showed a high sensitivity of more than 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in this study, most of the studies were conducted using external Holter monitoring as a criterion standard for the presence or absence of AF. Biotronik ILRs have evaluated the performance of AF algorithms through two separate studies [22,23]. As most of the AF episodes confirmed on the Holter were detected on the ILR, they showed a high sensitivity of more than 90%.…”
Section: Discussionmentioning
confidence: 99%
“…The improved detection of AF occurrence and AF characterization compared to intermittent ECG monitoring could significantly impact the clinical treatment decisions [16]. However, many studies on AF detection using ILRs have shown a lower-than-expected positive predictive value (PPV) due to a higher rate of false positive episodes [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…ECG is a field of rapid development of carriable devices, including implantable ones. [36][37][38][39] Some devices such as implantable cardioverter defibrillators require real-time classification of ECG data, which is a possible field of AI application. 40 These devices usually possess limited computational resources.…”
Section: Types Of Nn For Special Tasksmentioning
confidence: 99%
“…Unfortunately, using time-limited cardiac monitoring, such as the Holter monitor and external loop recorder (Seidl et al, 2000; Solbiati et al, 2016), the episodic and random nature of the arrhythmias and associated outcomes may not be captured. The ICM is one of the latest devices in long-term cardiac monitoring and may remain implanted for up to four years (Lauschke et al, 2016; Mittal et al, 2015), increasing the chances of capturing the heart rhythm at the time of the episode. The diagnostic yield of an ICM in undiagnosed syncope is between 43% and 52% compared to a device such as a Holter monitor, which only yields 6% to 20% detection (Kanters et al, 2016).…”
mentioning
confidence: 99%